Community engagement for birth preparedness and complication readiness in the Community Level Interventions for Pre-eclampsia (CLIP) Trial in India: a mixed-method evaluation. Issue 12 (20th December 2022) - Kavi, Avinash; Kinshella, Mai-Lei Woo; Ramadurg, Umesh Y; Charantimath, Umesh; Katageri, Geetanjali M; Karadiguddi, Chandrashekhar C; Honnungar, Narayan V; Bannale, Shashidhar G; Mungarwadi, Geetanjali I; Bone, Jeffrey N; Vidler, Marianne; Magee, Laura; et al.
Abstract : Objective: To describe the process of community engagement (CE) in northern Karnataka, India and its impact on pre-eclampsia knowledge, birth preparedness and complication readiness, pregnancy-related care seeking and maternal morbidity. Design: This study was a secondary analysis of a cluster randomised trial of Community Level Interventions for Pre-eclampsia (CLIP). A total of 12 clusters based on primary health centre catchment areas were randomised to intervention or control. CE was conducted in intervention clusters. CE attendance was summarised according to participant group using both quantitative and qualitative assessment. Pre-eclampsia knowledge, birth preparedness, health services engagement and perinatal outcomes was evaluated within trial surveillance. Outcomes were compared between trial arms using a mixed effects logistic regression model on RStudio (RStudio, Boston, USA). Community feedback notes were thematically analysed on NVivo V.12 (QSR International, Melbourne, Australia). Setting: Belagavi and Bagalkote districts in rural Karnataka, India. Participants: Pregnant women and women of reproductive age, mothers and mothers-in-law, community stakeholders and male household decision-makers and health workers. Results: A total of 1379 CE meetings were conducted with 39 362 participants between November 2014 and October 2016. CE activities may have had an effect on modifying community attitudes towards hypertension in pregnancy and its complications. However, rates of pre-eclampsia knowledge, birth preparedness, health services engagement and maternal morbidities among individual pregnant women were not significantly impacted by CE activities in their area. Conclusion: Evaluation of our CE programme in India demonstrates the feasibility of reaching pregnant women alongside household decision-makers, community stakeholders and health workers. More research is needed to explore the pathways of impact between broad community mobilisation to strengthen support for maternal care seeking and clinical outcomes of individual pregnant women. Trial registration number: NCT01911494 .